2023
DOI: 10.1186/s12906-023-03852-w
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antiproliferative potentials of phenolic-rich extracts from biotransformed grape pomace in colorectal Cancer

Abstract: Background Colorectal carcinoma is one of the most commonly diagnosed malignancies worldwide. Consumption of dietary supplements and nutraceuticals such as phenolic compounds may help combat colorectal carcinoma. The effect of two phenolic-rich extracts prepared from biotransformed grape pomace on the antioxidant properties and antiproliferative activity against two colorectal cancer cell lines (Caco-2 and SW620) were investigated. Methods A 15-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The key role of natural antioxidants in biological systems and their relationship with the treatment and prevention of various diseases has been the focus of nutrition and health researchers 4 , 5 . Natural antioxidants in food have shown positive effects in the prevention and treatment of many types of cancer 6 , 7 . It also prevents metabolic disorders by eliminating free radicals 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The key role of natural antioxidants in biological systems and their relationship with the treatment and prevention of various diseases has been the focus of nutrition and health researchers 4 , 5 . Natural antioxidants in food have shown positive effects in the prevention and treatment of many types of cancer 6 , 7 . It also prevents metabolic disorders by eliminating free radicals 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also revealed that the damage upon HT-29 was less pronounced, while the purified extracts appeared to have a higher activity than the crude extracts; finally, the purified grape extracts showed a higher specificity on the colorectal cancer cells compared to the fibroblast cell line CRL2072 [178]. Other studies on several phenolic-rich extracts from biotransformed grape pomace tested on colorectal cancer cell lines Caco-2 and SW-620 have also proved the ability of the GP products at 1.75 mg/mL and 2.5 mg/mL to inhibit the viability of the tested cells by more than 60%; the effects upon the Caco-2 line were less pronounced than those upon the SW620 line [179]. The present MTS cytotoxicity assay after 24 h of cell exposure also indicated the ability of the 50% ethanolic extracts from the fresh green seedless table grapes (EEG at t = 0 and t = 7) to inhibit the growth of the human colon carcinoma cell line Caco-2 along the entire interval tested: from 3.59 to 28.68 µg GAE/mL sample, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The products from grapes, mainly the grape pomace (GP) beverages, are some of the most studied fruits in relation with human health consumption and benefits [164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179]. Regarding the organ targeted effects, the literature data lean towards major benefits in counteracting the cardiac and coronary heart diseases [164][165][166][167][168][169][170][171][172][173].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that phenolic compounds have antiproliferative activity, and our previous work demonstrated that phenol-rich grape pomace extract from Cabernet Sauvignon affects the reduction of cell viability of Caco-2 and SW 620 cancer cell lines [40]. In the present study, the human liver cell line HepG2 and the colon cell lines Caco-2 and SW620 were used to evaluate cell viability in the presence of grape pomace-enriched biscuits (Figure 3).…”
Section: Antiproliferative Activity Of Biscuitsmentioning
confidence: 89%